2018
DOI: 10.29196/jubpas.v26i10.1865
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Paleostress Orientations and Magnitudes for Missan Structures, Southeastern Iraq

Abstract: The use of  Right dihedral method and Mohr diagram method allow determination of the paleostress orientation and its magnitude in Missan structures, Southeastern Iraq. The principal stress orientations and its magnitudes have been determined by the measure of the striation on the faults planes. The measurement of orientation of the principal stress was deduced by different graphical methods, the horizontal maximum principal stresses (?1) magnitudes were (3600, 4360,4650, 4750 and 5700) bars, the horizontal  in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Many authors studied cohesion strength of the sedimentary rocks and they showed that the range of the cohesion strength magnitudes is between zero (0) bars (the rock is broken), with no stick between the two blocks of faults, and (100) bars [1], [2], [3], [4], [5], [14], [15], [22], [23], [24] and [25]. According to the compilations used by several authors, the internal friction angle (ϕ) for the sedimentary rocks is (45°) [1], [2], [3], [4], [5], [14] and [15]. Under the above determination, which is based on rupture friction analysis that depends on the stress ratio, the sliding friction angles and the vertical stress have directly resulted in the measurements of the magnitudes of the paleostresses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors studied cohesion strength of the sedimentary rocks and they showed that the range of the cohesion strength magnitudes is between zero (0) bars (the rock is broken), with no stick between the two blocks of faults, and (100) bars [1], [2], [3], [4], [5], [14], [15], [22], [23], [24] and [25]. According to the compilations used by several authors, the internal friction angle (ϕ) for the sedimentary rocks is (45°) [1], [2], [3], [4], [5], [14] and [15]. Under the above determination, which is based on rupture friction analysis that depends on the stress ratio, the sliding friction angles and the vertical stress have directly resulted in the measurements of the magnitudes of the paleostresses.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors [2,3,4,5,14,15] used the fault slip data to calculate directions of the paleostress field.…”
Section: Methodology 1: Faults Orientation Determination Using Right Dihedral Methodsmentioning
confidence: 99%
“…The fault slip data was utilized by several authors such as Al-Obaidi [10]; Al-Diabat [19]; Al-Obaidi, and Al-Kotbah [11]; Al-Hachem, and Al-Obaidi [12] and Al-Shwaily and Al-Obaidi [20] to calculate trends of the paleostress field. The right dihedral approach was used to identify the trend of the study area's principle stresses axes (1, 2, and 3).The maximum principal stress (σ1) and the intermediate principal stress (σ2) were horizontal, while the minimum principal stress (σ3) was sub-vertical.…”
Section: Methodsmentioning
confidence: 99%